Physicochemical Characteristics of Milk and Teat Yield of Different Goat Breeds Under Normal Tropical Rearing Conditions (KARAKTER FISIKOKIMIA SUSU DAN PRODUK PUTING BERBAGAI RAS KAMBING YANG DIPELIHARA DALAM SUASANA TROPIS NORMAL DI FILIPINA) - Layola, Mari Denise Amphy Anoos; De Asis, Gary Rebadomia; Pena Jr., Santiago Torda (Jurnal Veteriner; Vol 21 No 1 (2020)DO - 10.19087/jveteriner.2020.21.1.53, 2020)
The use of imported high-yielding exotic breeds of goats under sub-optimal conditions either as a substitute to less productive local breeds or for upgrading puposes is not new. However, there is a needto enhance the production potential of these goats given the existing management practices and feeding conditions in order to realize their full economic impact. Using 41 clinically healthy lactating goats from seven different breeds including upgrades, and collected every week for eight consecutive weeks, our studydemonstrates how these exotic breeds perform under normal tropical rearing conditions in terms of physicochemical characteristics of milk and teat yield. For the milk yield, Saanen (397.8 ± 40.1 mL), Toggenburg(310.2 ± 28.6 mL) along with Alpine (297.1 ± 27.9 mL) topped all the breeds while the lowest was in upgrades (178.8 ± 7.8 mL; P < 0.05). There were no significant differences in the physicochemical characteristics of milk between the left and right udder halves except where pH was higher and calcium was lower in the left udder half (P < 0.05), respectively. Similarly, results show that both milk labeled as ‘good’ and ‘bad’ had relatively similar values for solids-not-fat, calcium, phosphorus, and density (P > 0.05)except for pH and fat content which were higher in milk samples labelled as ‘bad’ (P < 0.05). Such information could be useful to prospecting goat farmers especially for those in the goat milk processing industry.